Spelling first : Word-level activities in context across the curriculum / 1 - Barker, Ray; Moorcroft, Christine (Cheltenham : Nelson Thornes, 2002)
This supplementary series of textbooks and teacher files has been developed to encourage confident writers in secondary schools, meeting the need of effective literacy that has been identified as the key to raising standards across all curriculum areas.
Keywords: English language -- Orthography and spelling; English language -- Orthography and spelling Study and teaching (Elementary); Anglais (Langue) Orthographe Problèmes et exercices